Fluctuations of vegetation and climate over the last 75 000 years in the Savanna Biome, South Africa: Tswaing Crater and Wonderkrater pollen sequences reviewed. (1st August 2016) - Scott, L.
Abstract: Quaternary palynological information from the Savanna Biome of South Africa is limited due to the scarcity of suitable pollen traps and new extensive pollen records of palaeoenvironments in the region are unlikely to be obtained easily. Those that are available, including the Tswaing Crater and the Wonderkrater spring sequences, can, however, be reassessed and their data optimised. These two pollen records are relevant to palaeo-environmental research in the area, although they have chronologies beyond the radiocarbon dating range that complicate interpretations. The Tswaing sequence in this study focuses on the upper 34 m of pollen-rich layers out of a total of 90 m of lake deposits. A new chronology is experimented with for this upper part of the sequence. It differs slightly from the previous one in that it does not rely on adjustments of the ages according to the precession cycle. Accordingly the age at 34 m is estimated to be c. 75 ka based on interpolation of the radiocarbon sequence and a basal fission track date of c. 200 ka at 90 m. In the case of the second site, Wonderkrater, recently published excavation and dating of the deposits and comparisons with the Tswaing pollen sequence provide new clues for the age of the lowermost deposit of the original borehole sequence of peats, sands and clay, which is estimated at c. 60 000 years. The new results better situate the two pollen sequences in a wider regional and global palaeoenvironmental framework. Highlights: New chronological models proposed for two long sub-Saharan pollen records. Palaeoenvironmental sequences correlated to strengthen regional savanna record over 75 ka. MIS1-4 climate change in subtropical vegetation related to marine records in the Indian Ocean. Pollen taxonomy revised and counts presented as appendices.